ANALISIS PENGARUH KONFIGURASI TULANGAN TERHADAP KEKUATAN DAN DAKTILITAS KOLOM BETON BERTULANG - Sudarsana, I K. (Jurnal Ilmiah Teknik Sipil; Vol. 14, No. 1 Januari 2010)
Column is one of important structural elements to ensure that the structure will not suffer progressive collapse. In earthquake resistant design, column must have an adequate strength and ductility to provide ductile behavior to desipate earthquake forces on the structure. Strength and ductility of columns depend on many factors such as reinforcement arrangements. This analysis is done to investigate the effect of longitudinal dan transversal reinforcement arrangement on strength and ductility of reinforced concrete columns. Two groups of 4 specimens each, total 8 column sections were analized both with and without considering concrete confinement. In this analysis, stress-strain concrete model for unconfined concrete follows Honestaad Model (1951) and for confined concrete model follows Razvi and Saatcioglu Model (1999). Stress-strain of reinforcement is assumed to be a bilinear relationship. In the analysis of displacement ductility, the column height was taken of 3.5 meter behaving double curvature. Comparison of the results shows that for constant longitudinal reinforcement ratio (rl), arrangements of longitudinal bars distributed uniformly along the column sides has no significant effect on strength and ductility of the column section both for unconfined and confined section analysis. Hoop configuration gives an increase in strength (Mn), curvature ductility (?j) and displacement ductility (?D) on average about 1.2%, 2.3% and 1.83% if they are analyzed without considering confinement effects. However, the increase in those parameters is about 1.2%, 12%, 9.4% for strength (Mn), curvature ductility (?j) and displacement ductility (?D) if considering the effects of confinement. In general, the effect of hoop confinement on column section can increase in column strength and ductility on average of 0.25%, 158% and 98% respectively for strength, curvature and displacement ductilities.
Keywords: Pengekangan, Kekuatan, Daktilitas, Kolom, Beton Bertulang.